VITAMIN D INTOXICATION IN 7-MONTH-OLD INFANT WITH RECOMMENDED DAILY INTAKE OF VITAMIN D - Waheed, Nadia; Cheema, Huma Arshad; Saeed, Anjum; Alvi, Muhammad Arshad; Fayyaz, Zafar; Anjum, Nadeem; Batool, Sara (Journal of Ayub Medical College Abbottabad, 2019)
Over the past decade there is increased use of vitamin D supplementation because of its benefits on bone health. It is a fat-soluble vitamin and cannot be excreted from the body. There is need for monitoring 25-hydroxyvitamin D levels in infants and children who receive long-term vitamin D supplementation at or above the upper level intake that is currently recommended. Vitamin D intoxication can present from mild ignorable to severe life-threatening symptoms. We present a 7-month-old infant with vitamin D intoxication at recommended daily doses of vitamin D. Keywords: Hypervitaminosis D; Recommended daily allowance; Hypercalcemia, Vitamin D